Etiology, Diagnosis, Clinic and Treatment of Cutaneous Leishmaniasis (Eurasian Medical Research Periodical, 2022)
Cutaneous leishmaniasis can present with localized, chronic, recurrent, diffuse, and sharp forms. For diagnostics, dermatoscopy, microscopy of biopsy material, smears - prints, skin scrapings; inoculation on NNN medium, PCR, serological diagnostics. 4 types of histological manifestations of infection are characteristic: I - abundant amastigotes, II - macrophages, polymorphonuclear neutrophils, plasma cells, necrosis, III – early granuloma with focal accumulation of epithelial cells, lymphocytes and a small number of plasma cells, IV - well-formed epithelioid granuloma in the dermis with Langerhans giant cells, lymphocytes and epithelioid cells. First line drugs for cutaneous leishmaniasis are preparations of pentavalent antimony: sodium stibogluconate intravenously or intramuscularly, meglumine antimonate intravenously or intramuscularly, miltefosine orally